Evaluation of Application of Nutritional Status Assessment for Children Under 5 years by Using IMCI Program in a Sample of Primary Health Care Centers in Baghdad City - Raoof, Samir M.; Raoof, Rana D.; Ibraheem, Mohammed A. (AL-Kindy College Medical Journal, 2019)
Background: World Health Organization (WHO) and United Nation International Children Fund (UNICEF) developed a strategy known as Integrated Management of Childhood Illness (IMCI); which aims to reduce less than five years children morbidity and mortality in developing countries.Objective: To assess the completion of the IMCI format status in primary health care centers, Baghdad.Methods:  A cross sectional study with analytic element was conducted during the period from 15th  of January till 15th  May 2016 in selected Primary health centers in Baghdad, Iraq. The sample consists of form of child files less than 2 months and form from 2 month up to 5 years children. Classified correctively, determined follow up visits, Comparison classified of nutritional status assessment between health center and IMCI guideline.Result: 1400 child files were collected, 1295 from child files (2months-5year), and 105 forms from child less than 2 month. In form less than 2 months (correct classified 54.29%, incorrect 45.71%), (Determined date of follow up 13.33%, not determined 86.67%).Form from (2month-5years) (57.07% correct classified, 43.93% incorrect classified), (Determined date Follow up visit 38.38%, Not determined visit 61.62%).Conclusion: Impaired classification of nutritional status assessment